Measurement of the hydrodynamic radii of PEE‐G dendrons by diffusion spectroscopy on a benchtop NMR spectrometer. (30th January 2020) - McCarney, Evan R.; Breaux, Carol J.; Rendle, Phillip M.
Abstract: Benchtop nuclear magnetic resonance (NMR) spectroscopy is a useful tool for the rapid determination of the self‐diffusion coefficient and the hydrodynamic radius of dendrons. The self‐diffusion coefficients of the first four generations of poly ethoxy ethyl glycinamide (PEE‐G) dendrons are measured by diffusion‐ordered spectroscopy (DOSY) on a benchtop NMR equipped with diffusion gradient coils. The hydrodynamic radii of the dendrons are calculated via the Stokes–Einstein equation. The effects of solvent and pH are determined with the hydrodynamic radius increasing with generation and decreasing upon neutralization of an acidic solution. These measurements provide valuable information for biological and pharmaceutical applications of dendrons. Abstract : The benchtop nuclear magnetic resonance measurement of the self‐diffusion coefficients of a range of generations of poly ethoxy ethyl glycinamide dendrons by diffusion‐ordered spectroscopy is described. The hydrodynamic radii are calculated, and the effects of solvent and pH are reported.